2015
DOI: 10.1177/1368430215572265
|View full text |Cite
|
Sign up to set email alerts
|

Learning anxiety in interactions with the outgroup: Towards a learning model of anxiety and stress in intergroup contact

Abstract: While “knowledge learning” about the outgroup has been regarded as one of the key mechanisms for the contact–prejudice relation since the contact hypothesis’ first inception (Pettigrew & Tropp, 2008), “learning,” more broadly, has rarely been used as an explanatory framework to investigate the consequences of intergroup contact. In this article, we lay the foundation of a learning model of anxiety and stress in ingroup–outgroup interactions. We distinguish between episodic and chronic anxiety responses to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 112 publications
(193 reference statements)
4
57
0
1
Order By: Relevance
“…The ease, accessibility, and flexibility of progressively sophisticate LMSs to deliver tests encourages migrating assessments online. Wide-ranging, erodes academic achievement (Harpell & Andrews, 2013;Maloney et al, 2014;Paolini, Harris, & Griffin, 2016). Worry saps cognitive processing resources, such as attention, awareness, and working memory, which the test-taker would otherwise apply to the quiz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ease, accessibility, and flexibility of progressively sophisticate LMSs to deliver tests encourages migrating assessments online. Wide-ranging, erodes academic achievement (Harpell & Andrews, 2013;Maloney et al, 2014;Paolini, Harris, & Griffin, 2016). Worry saps cognitive processing resources, such as attention, awareness, and working memory, which the test-taker would otherwise apply to the quiz.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ongoing test anxiety fan mental health difficulties, peer detachment, and class disengagement (Hoffman, 2015). The social dynamics of online education-intrinsic impersonality and benign anonymity among cyber-dispersed students often completing work asynchronously-aggravate these circumstances as well as create new contingencies (Stowell & Bennett, 2010;DeBoer et al, 2014;Kena et al, 2014;Paolini, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although participants in the promotion condition had more positive contact experiences, and stereotyped their interaction partner less, we have no data on how these effects might generalize to the target group as a whole (i.e., people who have a history of schizophrenia) or on future intergroup contact (Paolini et al, 2014). We also have no data on how enduring these effects are over time (see also Paolini et al, 2016). Pettigrew (1998) suggested that it was important to consider the sequence of interventions over time.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, intergroup anxiety has negative consequences that include stereotyping, negative affect, and a desire to avoid future interactions (e.g., Islam and Hewstone, 1993; Greenland and Brown, 1999; Greenland et al, 2001; Brown and Hewstone, 2005; Turner et al, 2007; but see also Paolini et al, 2016). It can be experienced as “self-anxiety” (a fear that the participant will act or think in a way that makes them appear to be prejudiced) and as “other-anxiety” (a fear that the other represents a risk or a threat; Greenland et al, 2012; see also Plant and Devine, 1998; Stephan and Stephan, 2000).…”
Section: Intergroup Contact As An Intergroup Interventionmentioning
confidence: 99%
“…Abundant social psychological research demonstrates, on the other hand, that intergroup anxiety, intergroup concerns, and threats surrounding relationships with those we perceive as others contribute to intergroup bias, anti-immigrant attitudes, and dis-endorsement of multi-culturalism (see Paolini, Harris, & Griffin, 2016; Stephan, 2014 for reviews). Previous research indicated that anti-immigrant attitudes further predict opposition to EU-wide behaviours; research conducted found that anti-immigrant attitudes foster opposition to the EU and to European integration (Boomgaarden, Schuck, Elenbaas, & de Vreese, 2011;de Vreese & Boomgarden, 2005).…”
Section: Testing the Mediational Role Of Intergroup Threats And Genermentioning
confidence: 99%